Optimized conditions for callus induction, plant regeneration and alkaloids accumulation in stem and shoot tip explants of Phyla nodiflora - Ahmed, A.B.A.; Pallela, R.; Rao, A.S.; Rao, M.V.; Taha, R.M. (2011)
The present study describes callus induction and the subsequent plant regeneration with alkaloids accumulation in stern and shoot tip explants of Phyla nodiflora. Both explants were cultured on different media (MS, B5, SH and WPM) for callus induction. Stem explants showed better callus biomass (dry weight) than shoot tip explants with green compact callus when cultured on MS medium containing 1.5 mg L(-1) alpha-naphthalene acetic acid. Shoots were regenerated from the callus on MS medium with 1.5 mg L(-1) alpha-naphthalene acetic acid and 1.0 mg L(-1) benzyl adenine. The rooting of all regenerated shoots was successfully performed on half-strength MS medium with 1.0 mg L(-1) indole-3-butyric acid. The plantlets were acclimatized and established in soil (90) and exhibited morphological characteristics similar to those of the mother plant. In addition, the alkaloids content was higher in regenerated callus than intact stem and shoot tip explants, which were analyzed by a gravimetric method, TLC (thin layer chromatography) and HPTLC (high performance thin layer chromatography). The proposed method could effectively be applied for the conservation and clonal propagation to meet the pharmaceutical demands of this medicinally important species.